Metal ions from S‐PRG filler have the potential to prevent periodontal disease. Issue 4 (10th August 2017) - Iwamatsu‐Kobayashi, Yoko; Abe, Syouta; Fujieda, Yoshiyasu; Orimoto, Ai; Kanehira, Masafumi; Handa, Keisuke; Venkataiah, Venkata Suresh; Zou, Wei; Ishikawa, Masaki; Saito, Masahiro
Abstract: The surface pre‐reacted glass ionomer (S‐PRG) filler, a component of composite resin, is capable of releasing metal ions that possess antibacterial activity against caries and periodontal pathogens. Although S‐PRG has been suggested to be involved in oral disease prevention, no reports have been published regarding its preventive effect on periodontal disease in vivo . The present study investigated whether the eluate from S‐PRG (S‐PRG eluate) has a suppressive effect on tissue destruction induced in a mouse model of ligature‐induced periodontal disease. Twenty‐seven C57BL/6 mice were divided into three groups of nine animals each, no ligature group (Lig(−)), ligature group (Lig(+)S‐PRG(−)) and ligature with S‐PRG eluate group (Lig(+)S‐PRG(+)). Alveolar bone loss was evaluated using micro‐computed tomography scanning. Histologic changes were detected by hematoxylin and eosin staining. The infiltration of inflammatory cells was assessed by Ly6G and F4/80 staining immunohistochemically. The distribution of metal ions was detected by time‐of‐flight secondary ion mass spectrometry. S‐PRG eluate clearly inhibited alveolar bone loss and bone density. The histological analysis revealed that S‐PRG eluate reduced destruction of the collagen bundle in the periodontal ligament and the infiltration of inflammatory cells. Immunohistochemical analysis showed that the S‐PRG eluate significantly suppressed the number of infiltrating neutrophils and macrophages. Time‐of‐flight secondary ion mass spectrometry analysis revealed that more boron ions were present in the Lig(+)S‐PRG(+) group than in the Lig(+)S‐PRG(−) group. Our results suggest that the S‐PRG eluate has a preventive effect against tissue destruction in periodontal disease through its anti‐inflammatory effects in vivo .